Assessment of risk of falls in elderly living at home - Adriana de Azevedo Smith; Antonia Oliveira Silva; Rosalina Aparecida Partezani Rodrigues; Maria Adelaide Silva Paredes Moreira; Jordana de Almeida Nogueira; Luiz Fernando Rangel Tura
ABSTRACT Objective: to assess the risk of falls in elderly, by comparing the sociodemographic and cognitive factors, history of falls and self-reported comorbidities. Method: cross-sectional and quantitative study with 240 elderly. Data were collected based on the social profile, through the instrument of risk of falls and assessment of falls, by univariate analysis, bivariate and multiple logistic regression. The Statistical Package for the Social Sciences (SPSS) version 19 was used for statistical analysis. Results: there was a significant association of the risk of falls, as measured by the Fall Risk Score, with sex (<0.001), age (0.054), cognitive status (<0.001) and history of falls (<0.001). All variables were statistically significant and contributed to the occurrence of falls. In logistic regression, the variables that showed association with risk of falls were: fall, with whom they live, hypertension and visual impairment. Conclusion: female gender, older elderly (over 80 years old), with low cognitive status and occurrence of previous falls in the last six months are factors that increase the prevalence of falls. In logistic regression, the variables that were associated with risk of falls were: fall, with whom they live, visual impairment and rheumatologic diseases.